Analisis Economic Engineering Penggunaan Koagulan Natural-Based dan Koagulan Metal-Based dalam Pengolahan Air Bersih - Setyoningrum, Rahmadiah Indah; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Clean water treatment is always a challenge with the increasing pollution of water resources. This study focuses on an economic engineering approach in clean water treatment using various types of coagulants, namely using natural-based coagulants (moringa seed coagulant and maggot shell coagulant) and metal-based coagulants (alum coagulant). The main objective of this study is to analyze the comparison of technical aspects and cost aspects in the process of making coagulants and clean water treatment processes. This research method, in the technical aspect involves the coagulation-flocculation process in the removal of pH, turbidity, TSS, and color parameters, and in the cost aspect involves laboratory and industrial simulation methods to measure cost efficiency in coagulant production and clean water treatment by analyzing capital costs and operational costs. These results indicate that the use of natural-based coagulants, especially moringa seed coagulants, is more efficient overall than maggot shell coagulants and alum. Moringa seed coagulant can be 10-25% more cost-effective than maggot shell coagulant and alum, while maggot shell coagulant only provides a 15% cost savings in TSS processing compared to alum. Moringa seed coagulant is significantly more cost-effective because it has a low optimum dosage for processing pH, turbidity, TSS, and color, and is more environmentally friendly because it does not contain high levels of contaminants like metal-based coagulants.